2020
DOI: 10.18203/2320-6012.ijrms20200775
|View full text |Cite
|
Sign up to set email alerts
|

Detailed ECG analysis in type 2 diabetes mellitus: a predictor of multitude of complications

Abstract: Background: Type 2 diabetes mellitus is a systemic disease with life-threatening complications and morbidity. The 12 lead ECG, an easily available investigation, when studied in detail can give a lot of information and predict various microvascular and macrovascular complications apart from coronary artery disease.Methods: A random cross sectional study involving 100 patients of type 2 diabetes mellitus, in the age group of 18-80 years were included in study after applying various inclusion and exclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…other research works which reported more female participants than males(Gokhale & Jeyaseelan, 2020). The mean age of the experimental group in this study was 57.50 years.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…other research works which reported more female participants than males(Gokhale & Jeyaseelan, 2020). The mean age of the experimental group in this study was 57.50 years.…”
mentioning
confidence: 49%
“…This is in contrast to the result reported by Bedane et al (2021), which reported 200 (61%) having at least one type of ECG abnormality. Others reported 26% of subjects with ECG abnormalities, other studies reported 29.1% (Gokhale & Jeyaseelan, 2020) and 53% (Teimouri et al, 2022). The most common ECG abnormalities found in this population were ST-segment elevation, left ventricular hypertrophy (LVH), and left bundle branch block (LBBB).…”
Section: Ecg Abnormalities Associated With Type 2 Diabetesmentioning
confidence: 66%
See 1 more Smart Citation
“…The role of the ECG in diagnosing cardiovascular disease is crucial, including in diagnosing complications of diabetes other than coronary artery disease [11]. The high rate of asymptomatic ischemic heart disease [12] and the incidence of Left Ventricular Hypertrophy (LVH) [13] based on ECG examination makes the ECG examination a recommended diagnostic tool in detecting the risk of cardiovascular events [4].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple organ systems are affected by the disease, which is largely defined by hyperglycemia brought on by insufficient insulin secretion, ineffective insulin action, or occasionally a mix of both. It can lead to early atherosclerosis, which can damage both the micro-and macrovasculature and frequently manifest as nephropathy and coronary artery disease [4].…”
Section: Introductionmentioning
confidence: 99%